Arah Baru Politik di Era Digital (Perspektif Generasi Milenial di Media Sosial) - Dinda Aurellia; Katimin, Katimin (Yayasan Literasi Sains Indonesia, 2025)
The development of digital technology has significantly transformed the political landscape, particularly with the rise of social media as the primary platform for political interaction among the millennial generation. As a generation that grew up in the digital era, millennials tend to be more active in accessing, sharing, and discussing political issues through social media compared to conventional methods. This study aims to analyze how social media shapes millennials’ political perceptions and engagement while highlighting challenges such as the spread of hoaxes, opinion polarization, and low digital literacy. Using a qualitative descriptive approach, this research examines the patterns of political information consumption on social media and its impact on millennial political participation. The findings indicate that social media serves as a key tool in raising political awareness and mobilizing political support, but it also acts as a channel for misinformation, potentially influencing public political perceptions. Therefore, enhancing digital literacy is essential to ensure that millennials’ political participation is based on accurate and credible information. By understanding this digital political dynamic, this study is expected to provide insights for policymakers in designing more effective and inclusive political communication strategies for the millennial generation.